Treatment of Intrabony Defects by DFDBA Alone or in Combination with PRP: A Split-Mouth Randomized Clinical and Three-Dimensional Radiographic Trial - Hengameh Khosropanah; Shoaleh Shahidi; Amar Basri; Maral Houshyar (Tehran University of Medical Sciences, 2016)
Objectives:  The efficacy of adding platelet-rich plasma (PRP) to demineralized freeze-dried bone allograft (DFDBA) in order to improve the clinical and radiographic results obtained in treatment of deep periodontal intrabony defects has yet to be fully elucidated. Materials and Methods: This double blind, split-mouth randomized controlled clinical trial was conducted on 12 patients with two comparable bilateral intrabony defects. Each pair of defects was randomly treated with DFDBA+PRP (test) or DFDBA alone (control).  Clinical attachment level (CAL), intrabony defect depth (IDD), distance from the stent to the alveolar crest and pocket depth (PD) as well as radiographic parameters including the radiographic defect depth, width and angulation were measured at baseline and six months post-operatively. The paired t-test was used to compare the pre and post-treatment values and the unpaired t-test compared the test and control groups. Results: The mean reductions in PD and CAL were 4.5 ±1.3 mm and 3.6±1.6 mm in sites treated with DFDBA+ PRP, respectively (P<0.01); these reductions were 4.1±1.4 mm and 3.5±1.3 mm, respectively in DFDBA group (P<0.01). Radiographic evaluation revealed 2.5±1.1 mm reduction in the radiographic defect depth in the test and 2.1±1.2 mm in the control sites. The defect angulation increased at both sites. Statistically, there were no significant differences between the two treatment modalities (P<0.01). Conclusion: This study showed that both treatments resulted in significant PD reduction, CAL gain and IDD reduction. Also, PRP failed to enhance the results obtained by DFDBA. Key words: Cell- and Tissue-Based Therapy; Allografts; Cone-Beam Computed Tomography; Platelet-Rich Plasma